POLA ASUH ORANG TUA DAN KESEHATAN MENTAL REMAJA : IMPLIKASI BAGI PENGEMBANGAN KONSELING INDIVIDUAL DAN KELOMPOK BERBASIS ISLAM - Herwantoro; Dina Hajja Ristianti; Sumarto (STKIP Subang, 2026)
This study aims to determine the influence of parenting styles on the mental health of adolescents in Suka Mulya Village, Sumber Harta District, Musi Rawas Regency. The study employed a quantitative approach with a correlational research design using simple linear regression analysis. The population consisted of adolescents aged 12–15 years in Suka Mulya Village, with a sample of 30 respondents selected through purposive sampling techniques. Data collection was conducted through questionnaires regarding parenting styles and adolescent mental health. The data were analyzed using descriptive statistics, validity tests, reliability tests, normality tests, simple linear regression, t-tests, and the coefficient of determination. The results of the study indicate that parenting styles have an influence on adolescent mental health. Democratic parenting tends to have a positive effect on adolescents’ emotional stability, social skills, and self-control. In contrast, authoritarian and permissive parenting styles tend to be associated with increased anxiety, emotional instability, and lower social adaptation abilities among adolescents. The regression analysis results show a significant influence of parenting styles on adolescent mental health.